O paraíso atrasado: a construção do rural no Brasil através do imaginário geográfico - Maia, Adriano Corrêa [UNESP] (2015)
The work consists of an investigation, through a set of images for the country space, the historical construction of what we call rural. Thus, by analyzing a spatial imagination that took place on rural in Brazilian history, we point out some elements that can contribute to the understanding of its development and expropriations suffered historically. As a result we launched the ideas to the debate that the countryside was built as a subordinate element within the urban dynamics of the processes of the capitalist mode of production, which is building held by imposing a spatial imaginary organized into a single characterization based in a triad of ideological elements: modernity, urbanity and eurocentrism, with this imaginary on rural implying an action about space, a space imagination, building rural as placed in a circularity process